A transformada de Laplace e algumas aplicações - Lustosa, José Ivelton Siqueira Lustosa (2017)
In this work, we study the Laplace Transform and explore its application in solving some linear ordinary di erential equations, which model various phenomena in the areas of Physics, Engineering, Industrial Automation and Mathematics itself. Such knowledge is of great importance in higher education courses covering such areas. We present the de nition, properties and main results involving the Laplace Transform and address several problems in the areas mentioned above.